BIO-SUPERPHOSPHATE (BIO-SP) APPLICATION ON SUGAR CANE (Saccharum officinarum L.) - Goenadi, Didiek Hadjar; Santi, Laksmita Prima (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2013)
The highest expense on sugarcane management is fertilization in which one of them is phosphate fertilizer produced by imported raw materials. An innovation was made by using the local phosphate deposits with low reactivity processed further to improve their effectiveness for sugarcane. The objective of this study was to investigate the growth, yield and quality of sugarcane as affected by bio-superphosphate (Bio-SP) application on a highly weathered tropical soil. A nine-month field experiment was conducted at Jatitujuh Sugar Mill area, West Java, Indonesia, comparing between sugarcane fertilized with Bio-SP to replace conventional single superphosphate (SP-36) and that fertilized with SP-36. Urea and MOP (Muriate of Potash) were applied at similar dosages as recommended by division of Jatitujuh Sugar Mill Agronomy Research. Bio-SP was formulated by reacting a Central Java Rock Phosphate with liquid culture supernatant (LCS) and phosphoric acid characterized by 33% total soluble P2O5, 23.1, and 10.7 % citric acid and water-soluble P2O5, respectively. The results indicated that Bio-SP at 50% dosage of SP-36 was as effective as the SP-36 in supporting sugarcane growth and improved yield up to 8% as crystal sugar. Further consequence of this finding is that the application of Bio-SP reduced 9.2% of fertilizer cost for sugarcane. Keywords: microbial enrichment, highly weathe-red soils, fertilizer efficiency